GLOBAL VALUE CHAIN ​​GOVERNANCE OF INDONESIAN PEPPER: A CASE STUDY IN BANGKA BELITUNG - Andi Tenri Darhyati; Rita Nurmalina; Tanti Novianti; Suharno Suharno (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2026)
Pepper is one of Indonesia's primary plantation commodities, contributing significantly to global trade; however, its competitiveness continues to face challenges. An analysis of the governance structure within the pepper global value chain is essential to understand inter-actor relationship, power distribution, and decision making mechanisms that directly influence value creation and Indonesia’s position in international markets. This study aims to identify and analyze the governance structure of the pepper global value chain through a case study in Bangka Belitung Province in 2024. The study utilizes primary data collected from 63 respondents, compricing farmers, intermediary traders, and exporters. A quantitative descriptive approach based on the Global Value Chain (GVC) framework is employed, using a survey method targeting white pepper value chain actors. Value chain governance is analyzed using the GVC governance typology, which assesses transaction complecity, the degree of codification, and supplier capabilities, all measured using a Likert scale. The results indicate that the governance of the pepper value chain in Bangka Belitung is classified as relational, characterized by high transaction information complexity, low actor capacity for information codification, and strong capabilities in raw material supply. These characteristics lead to interactions among actors relying on trust-based relationships, personal influence, and informal coordination mechanisms. The policy implications emphasize the importance of institutional strengthening, quality standardization, capacity building of local actors, and the development of traceability and transparency systems. Such governance reforms are necessary for Indonesia to enhance its bargaining position, expand market access, and sustainably strengthen the competitiveness of pepper exports.